Association of phylogenetic distribution and presence of integrons with multidrug resistance in Escherichia coli clinical isolates from children with diarrhoea - Yesmi Patricia Ahumada-Santos; María Elena Báez-Flores; Sylvia Páz Díaz-Camacho; Magdalena de Jesús Uribe-Beltrán; Carlos Alberto Eslava-Campos; Jesús Ricardo Parra-Unda; Francisco Delgado-Vargas (Elsevier, 2020)
Background: Escherichia coli strains include both commensal and virulent clones distributed in different phylogenetic groups. Antimicrobial resistance is an increasingly serious public health threat at the global level and integrons are important mobile genetic elements involved in resistance dissemination. This paper aims to determine the phylogenetic groups and presence of class 1 (intl1) and 2 (intl2) integrons in E. coli clinical isolates from children with diarrhoea, and to associate these characteristics with their antimicrobial resistance. Methods: Phylogeny and presence of integrons (intl1 and intl2) were analysed by PCR and amplicon sequencing in 70 E. coli isolates from children with and without diarrhoea (35 of each group) from Sinaloa, Mexico; these variables were analysed for correlation with the antimicrobial resistance profile of the isolates. Results: The most frequent phylogroups were A (42.9%) and B2 (15.7%). The E. coli isolates from children with diarrhoea were distributed in all phylogroups; while strains from children without diarrhoea were absent from phylogroups C, E, and clade I. The 17.1% of the isolates carried integrons (15.7% intI1 and 1.4% intI2); 28.6% of the isolates from children with diarrhoea showed the class 1 integron. Strains of phylogroup A showed the highest frequency of integrons (33.3%). The association of multidrug resistance and the presence of integrons was identified in 58.3% of strains isolated from children with diarrhoea included in phylogroups A and B2. The sequence analysis of intl1 and intl2 showed silent point mutations and similarities with plasmids of some APEC and AIEC strains. Conclusion: Commensal E. coli strains are potential disseminators of antimicrobial resistance, and the improvement in the use of antimicrobials to treat childhood diarrhoea is essential for the control of such resistance. Keywords: Escherichia coli, Phylogeny, Integrons, Antimicrobial resistance, Diarrhoea